Racism towards Black American: Intersectionality in Constructing Social Racist through Poetical Depiction by Langston Hughes and Amy Saunders - Ni Luh Nyoman Seri Malini; I Gusti Ayu Sundari Okasunu; Made Detriasmita Saientisna (Journal of Language and Literature, 2021)
In this research, the development of racism based on the different formations of socio-cultural and historical aspects was the standpoint that was shown by the interpretation of poetical depiction of meaning and messages. The gap between Langston Hughes in “I, too, sing America” (1926) and Amy Saunders in “You’re not Black” (2019) as the data advocates for racist transformation in natural past and present American socialization. Several critical studies have examined the racial issues reflected in poems however they didn’t elaborate on racism specifically rather than segregation and discrimination although racism is classified in several types. Moreover, the critical studies have been done only analyzed the racism happened on the past while this study compares the past and present racism as the concern of social construction among black American as the target of unfair treatments. The descriptive qualitative method using documentation, descriptive analysis, and note-taking technique was used to identify and elaborate meaning correlation with racial issues in the poems. This research aimed to classify the figurative language and its meaning related to racism while illustrating the development of racism from the perspective of socio-cultural and historical aspects that influenced the poets and their poetry. Theory of Critical Race was used to demonstrate that racism was developing in a different formation. The research has found the interconnection between historical values of slavery system constructed stereotypes of black people as minor American. Social construction formed a cultural differentiation which led to segregation and discrimination towards black in any form of everyday aspects.